Advanced research trends in dye-sensitized solar cells. Issue 17 (18th March 2021) - Kokkonen, Mikko; Talebi, Parisa; Zhou, Jin; Asgari, Somayyeh; Soomro, Sohail Ahmed; Elsehrawy, Farid; Halme, Janne; Ahmad, Shahzada; Hagfeldt, Anders; Hashmi, Syed Ghufran
Abstract : Dye-sensitized solar cells (DSSCs) are an efficient photovoltaic technology for powering electronic applications such as wireless sensors with indoor light. Abstract : Dye-sensitized solar cells (DSSCs) are an efficient photovoltaic technology for powering electronic applications such as wireless sensors with indoor light. Their low cost and abundant materials, as well as their capability to be manufactured as thin and light-weight flexible solar modules highlight their potential for economic indoor photovoltaics. However, their fabrication methods must be scaled to industrial manufacturing with high photovoltaic efficiency and performance stability under typical indoor conditions. This paper reviews the recent progress in DSSC research towards this goal through the development of new device structures, alternative redox shuttles, solid-state hole conductors, TiO2 photoelectrodes, catalyst materials, and sealing techniques. We discuss how each functional component of a DSSC has been improved with these new materials and fabrication techniques. In addition, we propose a scalable cell fabrication process that integrates these developments to a new monolithic cell design based on several features including inkjet and screen printing of the dye, a solid state hole conductor, PEDOT contact, compact TiO2, mesoporous TiO2, carbon nanotubes counter electrode, epoxy encapsulation layers and silver conductors. Finally, we discuss the need to design new stability testing protocols to assess the probable deployment of DSSCs in portable electronics and internet-of-things devices.